Preliminary Experience With a Minimally Invasive Technique for Hallux Valgus Correction With No Fixation. (January 2020) - Lucattelli, Giuseppe; Catani, Ottorino; Sergio, Fabrizio; Cipollaro, Lucio; Maffulli, Nicola
Background: Percutaneous operative techniques for hallux valgus (HV) correction are less damaging to soft tissues and the first metatarsophalangeal joint, and they carry a lower risk of wound complications. We report our preliminary results using a percutaneous technique that allowed correction of the deformity without internal fixation. Methods: One hundred ninety-five consecutive patients with isolated symptomatic HV were surgically treated using a percutaneous technique without any form of internal fixation, with a mean follow-up of 34.6 months. The American Orthopaedic Foot & Ankle Society (AOFAS) hallux-metatarsophalangeal-interphalangeal scale score was used for clinical assessment. Radiographic evaluation included pre- and postoperative assessment of the hallux valgus angle (HVA), intermetatarsal angle (IMA), distal metatarsal articular angle (DMAA), and sesamoid position in weightbearing radiographs. Results: According to the AOFAS score, the patients improved from a preoperative median of 54.7 to 89.6 at 2 years' follow-up ( P = .002). Patients were satisfied or very satisfied in 94% of cases at the latest follow-up. A mean radiographic correction of the HVA of 15.5 degrees, of the IMA of 5.4 degrees, and of the DMAA of 5.4 degrees was achieved. The AOFAS global score and every individual parameter improved significantly between pretreatment and latest follow-up ( P > .01). A total of 19 (9.7%) complications were reported. Conclusion: This percutaneous technique, which did not use any form of internal fixation described, produced durable results for the correction of HV, reliably correcting the deformity and resulting in significant improvement in function and decrease of pain. Level of Evidence: Level IV, retrospective case series.